Digital Signatures in a Quantum World: Evaluating The Trade-off Between Performance and Security for GeMSS - Reis, Paulo Ricardo; Borges, Fábio (Anais do Workshop de Regulação, Avaliação da Conformidade e Certificação de Segurança; 2019: Anais do V Workshop de Regulação, Avaliação da Conformidade e Certificação de Segurança, 2019)
With the advent of quantum computing, it urges the deﬁnition of a cryptographic standard algorithm that can resist attacks from a quantum computer. Inside this context is GeMSS, a multivariate quadratic signature scheme based on the HFEvconstruct. Schemes of this type have shown great potential throughout the last two decades. This paper traces a comparison of performance and security between GeMSS and other relevant digital signature schemes, showing that despite of its slow signature generation and large key pair, it has a very quick veriﬁcation process and tiny signatures. It also proposes a method for deriving the size of keys from the security parameter evaluated.